Desarrollo de un metodo de seleccion de plantas por eficacia fotosintetica - Medrano, H.=700 1 Primo-Millo, E.
(Es, En)
ilus., 73 ref.
Keywords: FOTOSINTESIS; NICOTIANA TABACUM; SELECCION; HAPLOIDIA; ESPAÑA; EFICACIA FOTOSINTETICA